HUBUNGAN TINGKAT KEBISINGAN DENGAN STRESS KERJA PADA PEKERJA PABRIK BATU ALAM DI DESA KEPUH KABUPATEN CIREBON - Fajr Lintang Pinilih; Yani Kamasturyani; Akhmad Fauzi (LPPM ITEKES Mahardika, 2021)
Industrial Work Environment Health is an effort to prevent disease or health problems from risk factors in the industrial work environment consisting of physical, chemical, biological, ergonomic, and sanitary hazard factors to realize a healthy industrial work environment quality. The purpose of this study was to determine the relationship between noise level and work stress on natural stone factory workers in Kepuh Village, Cirebon Regency. This research method is quantitative using an observational analytical research design with a cross-sectional approach. The sampling technique used is total sampling. The sample used is all natural stone factory workers in the village of Kepuh, Cirebon district as many as 59 people. The instrument used in this research is to use a measuring instrument, namely Sound Level Meter and a questionnaire with the checklist method. The results showed that most of the production area of the noisy factory was (79.7%) the two variables were interrelated with the proven p value = 0.000. The conclusion of the study shows that there is a significant relationship between Noise Level and Work Stress on Natural Stone Factory Workers in Kepuh Village, Cirebon Regency.